DONGENG SEBAGAI PENDIDIKAN ANTI KORUPSI PADA ANAK USIA DINI - Sidik Nuryanto (Universitas Muhammadiyah Ponorogo, 2016)
Corruption is a major threat to the state. How many losses to be borne by the state due to the corrupt who takes people's money. Cases of corruption in Indonesia tends to increase every year. In order to tackle corruption is widespread need for anti-corruption education. Such efforts can be done either by entering the educational curriculum. Early childhood education as a strategic move, because at that age as a golden age that will be decisive for his future later. Anti-corruption education in early childhood can be achieved by a fairy tale. The relevance of the two is a fairy tale as entertainment and inculcate anti-corruption code. Spread the message of moral fairy tale without a child realizes he was injected with the values of kindness. Fairy tales become a way to realize the basic rule, that value investment can be done without being pushy and intimidating. Anti-corruption education in early childhood with fairy tales is to give a story or a fairy tale in which the charged knowledge, attitudes, and behaviors that anti-corruption. Value is a leading character in a fairy tale is the importance of honesty, and not greedy or avaricious. After the daily activities is to familiarize children with behavior in accordance with the anti-corruption fairytale. The hope after the children know the value of anti-corruption, also can apply it in a child's life.